2012
DOI: 10.1002/rra.2628
|View full text |Cite
|
Sign up to set email alerts
|

Using a Non-Physical Behavioural Barrier to Alter Migration Routing of Juvenile Chinook Salmon in the Sacramento-San Joaquin River Delta

Abstract: Anthropogenic alterations to river systems, such as irrigation and hydroelectric development, can negatively affect fish populations by reducing survival when fish are routed through potentially dangerous locations. Non-physical barriers using behavioural stimuli are one means of guiding fish away from such locations without obstructing water flow. In the Sacramento-San Joaquin River Delta, we evaluated a bio-acoustic fish fence (BAFF) composed of strobe lights, sound and a bubble curtain, which was intended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 14 publications
(16 reference statements)
3
63
0
6
Order By: Relevance
“…Alternatively, Perry et al . () found that a combined bubble–strobe‐light system was effective in diverting migrating Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792). Similarly, a 2012 study reported that a bubble–strobe‐light barrier was successful in preventing H. molitrix and H. nobilis from migrating upstream, but the researchers were unable to identify how many tagged fish remained in the area and challenged the barrier (Ruebush et al ., ), which makes this study difficult to evaluate.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, Perry et al . () found that a combined bubble–strobe‐light system was effective in diverting migrating Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792). Similarly, a 2012 study reported that a bubble–strobe‐light barrier was successful in preventing H. molitrix and H. nobilis from migrating upstream, but the researchers were unable to identify how many tagged fish remained in the area and challenged the barrier (Ruebush et al ., ), which makes this study difficult to evaluate.…”
Section: Discussionmentioning
confidence: 97%
“…Fish behavioural barriers have been commonly used for fish guidance, altering fish migration routines, in order to protect native species or to avoid and limit the spread of invasive alien species (Noatch & Suski, ; Perry et al ., ; Schilt, ; Vetter et al ., ). Several of such deterrence techniques have been used as management tools in freshwater systems including electrical, chemical, visual and acoustic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Perry et al (2012) and Welton et al (2002) demonstrated that acoustic-bubble barriers were effective at controlling downstream-migrating salmon smolts (Oncorhynchus spp.) Although less success was observed for upstream-swimming adult C. carpio, the result for downstream-swimming recruits is relevant because of its low cost, there are no alternatives to block downstream movement and that less than complete efficacy may often be acceptable for an already established species.…”
mentioning
confidence: 99%